A Long Spin Period for a Sub-Neptune-mass Exoplanet - Ellen M. Price; Juliette Becker; Zoë L. de Beurs; Leslie A. Rogers; Andrew Vanderburg (The Astrophysical Journal Letters)
HIP 41378 f is a sub-Neptune exoplanet with an anomalously low density. Its long orbital period and deep transit make it an ideal candidate for detecting oblateness photometrically. We present a new cross-platform, GPU-enabled code, greenlantern , suitable for computing transit light curves of oblate planets at arbitrary orientations. We then use the Markov Chain Monte Carlo method to fit K2 data of HIP 41378 f, specifically examining its transit for evidence of oblateness and obliquity. We find that the flattening of HIP 41378 f is f ≤ 0.889 at the 95% confidence level, consistent with a rotation period of P _rot ≥ 15.3 hr. In the future, high-precision data from JWST have the potential to tighten such a constraint and can differentiate between spherical and flattened planets.